Six seasons : a new way with vegetables - McFadden, Joshua; Holmberg, Martha (Artisan, 2017)
"In 225 simple, inventive recipes that celebrate all the ways to use all the parts of a vegetable at its peak, McFadden shares his passion and expertise as both chef and farmer"--Page 4 of overleaf.